IMPACT OF HYPERKERATOTIC PALMOPLANTAR DERMATOSES ON DERMATOLOGY LIFE QUALITY INDEX, IN A TERTIARY CARE CENTRE IN EASTERN INDIA: A CROSS-SECTIONAL STUDY. - Raut, Poonam; Saha, Pranab Kumar; Bhunia, Deblina; Singh, Priyanka (Student's Journal of Health Research Africa, 2024)
Background: Palmoplantar dermatoses viz., palmoplantar psoriasis (PPP), hyperkeratotic hand foot eczema (HHFE), and palmoplantar keratoderma (PPK) are the common concern in dermatology as being chronic nature of the dermatoses. Furthermore, they are recalcitrant to treatment and cause significant impairment in quality of life. Early diagnosis and prompt treatment help in improving the quality of life of a patient. Aim: To study the impact of hyperkeratotic palmoplantar dermatoses on quality of life. Materials and methods: A cross-sectional study was conducted. Patients of either sex, over 16 years of age presenting with hyperkeratotic lesions on palms and soles who were clinically diagnosed as palmoplantar psoriasis, hyperkeratotic hand foot eczema, palmoplantar keratoderma those were not under any topical or systemic medication within past 1 month were enrolled in the study. Quality of life was assessed by the Dermatology Life Quality Index (DLQI) questionnaire. Results: One hundred fifty-one patients were enrolled, of which 83 (55%) were males and 68 (45%) were females. palmoplantar psoriasis was the most common dermatosis with 74 (49%) patients, followed by hyperkeratotic hand foot eczema with 45(30%) patients and palmoplantar keratoderma with 32(21%) patients. Farmers and housewives were the most affected occupational group. The mean DLQI was maximum in hyperkeratotic hand foot eczema (13.31) followed by PPP (12.08) and PPK (9.15) being the lowest. The most common symptoms affected were feeling and work-related disability. Conclusion: Chronic palmoplantar dermatoses have significant impairment in quality of life. Recommendations: Early diagnosis and treatment of hyperkeratotic palmoplantar dermatoses, like PPP, HHFE, and PPK, are essential for improving quality of life. Using the Dermatology Life Quality Index routinely helps create personalized treatment plans and enhances patient outcomes.